The spectrum of spinal cord lesions in a primate model of multiple sclerosis. (March 2020) - Lefeuvre, Jennifer A; Guy, Joseph R; Luciano, Nicholas J; Ha, Seung-Kwon; Leibovitch, Emily; Santin, Mathieu D; Silva, Afonso C; Jacobson, Steven; Lehéricy, Stéphane; Reich, Daniel S; Sati, Pascal
Background: Experimental autoimmune encephalomyelitis (EAE) in the common marmoset is a nonhuman primate model of multiple sclerosis (MS) that shares numerous clinical, radiological, and pathological features with MS. Among the clinical features are motor and sensory deficits that are highly suggestive of spinal cord (SC) damage. Objective: To characterize the extent and nature of SC damage in symptomatic marmosets with EAE using a combined magnetic resonance imaging (MRI) and histopathology approach. Materials and Methods: SC tissues from five animals were scanned using 7 T MRI to collect high-resolution ex vivo images. Lesions were segmented and classified based on shape, size, and distribution along the SC. Tissues were processed for histopathological characterization (myelin and microglia/macrophages). Statistical analysis, using linear mixed-effects models, evaluated the association between MRI and histopathology. Results: Marmosets with EAE displayed two types of SC lesions: focal and subpial lesions. Both lesion types were heterogeneous in size and configuration and corresponded to areas of marked demyelination with high density of inflammatory cells. Inside the lesions, the MRI signal was significantly correlated with myelin content ( p  < 0.001). Conclusions: Our findings underscore the relevance of this nonhuman primate EAE model for better understanding mechanisms of MS lesion formation in the SC.